To multiply the polynomial \((b + 8)(3b - 6)\), we can use the distributive property (also known as the FOIL method for binomials):
-
First, multiply the first terms: \[ b \cdot 3b = 3b^2 \]
-
Next, multiply the outer terms: \[ b \cdot (-6) = -6b \]
-
Then, multiply the inner terms: \[ 8 \cdot 3b = 24b \]
-
Lastly, multiply the last terms: \[ 8 \cdot (-6) = -48 \]
Now, we combine all these results: \[ 3b^2 - 6b + 24b - 48 \]
Combine the like terms: \[ 3b^2 + ( -6b + 24b) - 48 = 3b^2 + 18b - 48 \]
Thus, the simplified polynomial is: \[ \boxed{3b^2 + 18b - 48} \]
Therefore, the correct response is: 3b^2 + 18b - 48 (or "3 b squared plus 18 b minus 48").